Influence of the Constitutional and Legal Science on the Formation of Modern Public Policy for Human Potential Protection - TORDIA, Inna Valentinovna; SAVCHENKO, Svetlana Antonovna (Journal of Advanced Research in Law and Economics, 2016)
The present article reveals the legal aspects of the social life of the population, identifies the problems affecting the formation of the public social policy, and suggests the forms of influence of the constitutional and legal science on the solution of the national problem. The authors propose a scientific approach to solving the problem of lack of the effective implementation of the public legal policy. The research discloses several problematic unresolved issues affecting the formation of public policy for human potential protection, some of which are the     expectancy and low quality of life of Russians and high mortality of the population, which make it a national problem, according to the authors. They study the aggregate data for the last 17 years, confirming the relevance of this issue for both the Voronezh and Tyumen regions. The authors also analyze scientific approaches of the health and medical science in the Russian Federation until 2020 and propose the ways of improving the efficiency of use of available resources.